Komisi Etik Penelitian di Perguruan Tinggi: Membangun Budaya Riset yang Bertanggung Jawab dan Berintegritas - Getut Pramesti; Sri Mulyani; Yusfia Hafid Aristyagama; Dewi Gunawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study critically examines the pivotal role of the Research Ethics Commission (KEP) in fostering a research culture grounded in responsibility and integrity within higher education institutions. Employing a mixed-methods design, the research integrates both quantitative and qualitative approaches. The quantitative phase utilizes a pre-post experimental design to assess the impact of KEP reviewer training on the knowledge enhancement of prospective reviewers at the Faculty of Teacher Training and Education. Data were gathered via structured questionnaires administered before and after the intervention, with statistical analysis conducted using paired t-tests, revealing significant improvements in reviewer comprehension (p < 0.01). Complementing this, the qualitative component involves a comprehensive literature review that elucidates the critical function of KEP in upholding ethical standards and research quality in academia. Findings from the literature reinforce KEP’s essential status as a cornerstone in cultivating an ethical and accountable research environment. The study highlights the importance of systematic reviewer training and robust policy enforcement within KEP to ensure the integrity and transparency of scholarly research in higher education settings.